2017
DOI: 10.1128/jvi.02412-16
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Receptor (TCR) Clonotype-Specific Differences in Inhibitory Activity of HIV-1 Cytotoxic T-Cell Clones Is Not Mediated by TCR Alone

Abstract: Functional analysis of T-cell responses in HIV-infected individuals has indicated that virus-specific CD8 ϩ T cells with superior antiviral efficacy are well represented in HIV-1 controllers but are rare or absent in HIV-1 progressors. To define the role of individual T-cell receptor (TCR) clonotypes in differential antiviral CD8 ϩ T-cell function, we performed detailed functional and mass cytometric cluster analysis of multiple CD8 ϩ T-cell clones recognizing the identical HLA-B*2705-restricted HIV-1 epitope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…Therefore, our results suggest that differences in CTL responses in HCs and CPs were not due to differences in functional properties of their TCRs. While our results extend considerably the studies recently reported by Flerin et al (27), they contrast with previous data showing divergent function in CTL clones from one HC (CTR203) and two CPs (CR338 and FEN33), from which TCRs HC25, CP27, and CP7.9 tested here were derived (8). Unfortunately, the original CTL clones are no longer viable, preventing their direct comparison with transduced T cells in our assays.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Therefore, our results suggest that differences in CTL responses in HCs and CPs were not due to differences in functional properties of their TCRs. While our results extend considerably the studies recently reported by Flerin et al (27), they contrast with previous data showing divergent function in CTL clones from one HC (CTR203) and two CPs (CR338 and FEN33), from which TCRs HC25, CP27, and CP7.9 tested here were derived (8). Unfortunately, the original CTL clones are no longer viable, preventing their direct comparison with transduced T cells in our assays.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, there is evidence to suggest that immunologic control of HIV may be a function of the TCRs that mediate HIV-specific immunity (26). A recent report based on data from a single HC indicated that clonotypespecific differences between CTLs are not dependent on their TCRs alone (27). However, those results do not address the role of TCRs in HIV control because they did not compare TCRs from HCs and CPs.…”
Section: Significancementioning
confidence: 98%
“…We show here that TCR affinity is also a key determinant of CD4 + T cell cytotoxic function, which has major implications for understanding the basis of HIV control. Recent findings suggest that cellular factors independent of TCR affinity may also contribute to the efficient cytolytic capacity of HIV controller CD8 + T cells (29). A limitation of our study is that we did not assess TCR-independent factors, such as the expression of costimulatory receptors.…”
Section: Discussionmentioning
confidence: 95%
“…HLA alleles associated with HIV control impart thymic selection for TCR repertoires with increased HIV recognition and variant cross-reactivity 65 . Although differential TCR usage alone is insufficient to explain spontaneous control or confer functional differences in CD8 + T cells [66][67][68] , cross-reactive TCRs have been shown to limit viral escape pathways in controllers, consistent with the findings that mutations within epitopes targeted predominantly by controllers are poorly tolerated due to impaired viral replication 69,70 and that their recognition is maintained in controllers by cross-reactive TCRs and de novo responses [71][72][73] .…”
Section: Cd8 + T Cell Specificity In Spontaneous Hiv Controlmentioning
confidence: 59%